Nicotinic acetylcholine receptor desensitization is regulated by activation-induced extracellular adenosine accumulation - Pitchford, S (J Neurosci, 1992)
Adenosine modulation of nicotinic ACh receptor (nAChR) function was studied in primary cultures of rat skeletal muscle. Activation of the nAChR by carbachol increased extracellular adenosine concentration in a dose-dependent manner. Furthermore, carbachol activation of the nicotinic receptor resulted in a twofold increase in cAMP levels in the muscle cells. The carbachol-dependent increase in cAMP levels was inhibited by adenosine receptor antagonists as well as by nicotinic receptor antagonists. These results suggest that the increased cAMP levels were due to adenosine receptor activation by the extracellular adenosine accumulated on nAChR activation. Others have shown that desensitization of the nAChR by agonist is mediated, in part, by phosphorylation. Since we found that nicotinic cholinergic agonists also cause adenosine accumulation with concomitant cAMP increases, we determined whether the accumulated adenosine has a role in desensitization. We found that the adenosine receptor antagonist, BW1434U, significantly inhibited carbachol-induced nAChR desensitization, indicating that extracellular adenosine is involved in nAChR desensitization. Our data suggest that nAChR function is regulated via a feedback mechanism mediated by adenosine released from muscle on activation of the nAChR.